Increased Cutting Conditions when Machining Heat-resistant Steel Using Indexable Inserts - Dostal, Pavel; Sadilek, Marek; Kusnir, Lukas; Kouril, Karel; Cep, Robert (Manufacturing Technology Journal, 2021)
The topic of the article is the increase of cutting conditions in the machining of heat-resistant steel using exchangeable inserts. The main part is the design of a new technology for machining one of the heat-resistant materials using replaceable inserts, including a discussion of any defects and economic evaluation. The aim is to reduce production costs and contribute to the elimination of production times. These modifications of technologies have a positive effect on the overall economy of produc-tion and the use of new methods in practice. Heat-resistant steels have found application in many branches of production, especially in the aerospace industry for jet engine components. Their specific properties need a more detailed examination of the optimal conditions for their processing.
Keywords: Heat-resistant steels; machining; cutting conditions; indexable inserts; aviation